Persepsi Sistem E-Business terhadap Jual Beli Online Shopee pada Mahasiswa: - Muhammad Resty Fauzi; Silvia Fransiska; Nurbaiti Nurbaiti (VISA: Journal of Vision and Ideas, 2023)
This study describes how the effect of the e-business system on Shopee online shopping transactions on students (Study on Febi Students, Islamic Banking Department, UIN North Sumatra). This study aims to determine how satisfied the Shopee online transaction is for Febi students majoring in Islamic Banking. The focal point in the discussion of this research is the description, price, level of service, and experience gained from both the seller and the courier of goods. This research was conducted using a qualitative descriptive method on students using Online Shopee and using a research theory in the form of Constructive Perception Theory. The results based on the research stated that there were students' perceptions of: (1) Overview; the expected product quality 4 students were not satisfied because the quality of the goods ordered was not in line with what they saw on Shopee and 13 students were satisfied with the expected product quality. (2) Price, from the quality of the product students are satisfied with the price, students are satisfied and do not feel burdened by the prices listed at Shopee. (3) the quality of service, 5 students were relatively satisfied with the service of employees/employees, and 5 students were not satisfied because the behavior and delivery program were less practical and subtle. (4) During service, students are satisfied with the delivery of goods, because they do not wait too long or it can be said that they are on time. Keywords: Perception, E-business, Online Shopping, Shopee